2012
DOI: 10.1111/j.1399-3089.2012.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation blockade in pig artery patch xenotransplantation – a simple model to monitor the adaptive immune response in nonhuman primates

Abstract: Background CD154-blockade-based immunosuppression successfully prevents both humoral and cellular adaptive immune responses in baboons receiving α1,3-galactosyltransferase gene-knockout (GTKO) pig organs. Using a GTKO pig artery transplantation model in baboons, we evaluated the efficacy of CD28/B7 costimulatory pathway blockade in comparison to CD154-blockade. Methods Baboons received artery patch grafts from GTKO pigs, with either no (Group1), anti-CD154mAb-based (Group2), or CTLA4-Ig-based (Group3) immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 27 publications
4
98
0
Order By: Relevance
“…Platelet activation and deposition in xenografts is a major feature of the dysregulation of the coagulation system after organ xenotransplantation (23,24). Additionally, we have observed platelet deposition in GTKO pig artery patch xenografts (5).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Platelet activation and deposition in xenografts is a major feature of the dysregulation of the coagulation system after organ xenotransplantation (23,24). Additionally, we have observed platelet deposition in GTKO pig artery patch xenografts (5).…”
Section: Discussionmentioning
confidence: 93%
“…As anti-CD154mAb is not available for clinical use, we investigated whether CD28/B7 costimulation pathway blockade using a CTLA4-Ig-based regimen can prevent sensitization to pig antigens after GTKO pig artery patch xenotransplantation in baboons (5). Both anti-CD154mAb-and CTLA4-Ig-based therapies were able to prevent cellular proliferation in response to pig cells and maintain low levels of CD4 + T cells and CD20 + B cells after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an anti-CD40 antibody associated with belatacept extended neonatal porcine islet survival (Thompson et al 2011b), although further studies are needed to confirm this finding. On the other hand, Ezzelarab et al (2012) found in an artery-patch xenotransplantation model that CTLA-4Ig therapy was probably not as efficacious as CD154/ CD40 inhibitors in preventing cellular and humoral response (Dons et al 2012).…”
Section: Systemic Immunosuppressionmentioning
confidence: 99%